Evaluation of Consumer Purchase Decisions at Cafe on the Wheels: What is the Role of Social Media Marketing, Brand Image, and Product Quality? - Fuadiyah, Alda; Suhud, Usep; Krissanya, Nofriska (LPPPIPublishing, 2025)
The purpose of this study was to determine the effect of social media marketing, brand image, product quality on purchase intention and purchase decision for consumers of café on the wheels Jago Coffee. The research method uses Quantitative with a survey approach. The sampling technique in this study used purposive sampling sampling with criteria. The criteria used are, have bought Jago Coffee at least once in the last 4 months, live in Jakarta City, know the existence of Instagram social media from Jago Coffee (@Jagoid) and have seen the content. The sample in this study were 303 respondents. The data analysis technique uses Structural Equation Modeling (SEM) through AMOS 23 software and SPSS version 25 to analyze and manage research data. The results of this study indicate that: first, social media marketing, brand image, product quality have a positive and significant effect on purchase intention. Second, social media marketing, brand image, product quality, and purchase intention have a positive and significant effect on purchase decisions.